2017
DOI: 10.18632/oncotarget.15315
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cell microRNA-based prognostic classifier for non-muscle invasive bladder cancer

Abstract: Current prognostic tools for non-muscle invasive bladder cancer (NMIBC) do not have enough discriminative capacity to predict the risk of tumour progression. This study aimed to identify urinary cell microRNAs that may be useful as non-invasive predictive biomarkers of tumour progression in NMIBC patients. To this end, 210 urine samples from NMIBC patients were included in the study. RNA was extracted from urinary cells and expression of 8 microRNAs, previously described by our group, was analysed by quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The incidence and mortality of bladder cancer have been significantly increased in the past decade [ 3 6 ]. Despite improvements in current clinical treatment such as surgery, adjuvant chemoradiotherapies, and immunological therapy, the prognosis of patients has not been significantly improved [ 7 11 ]. Patient's prognosis is closely related to the stage of the disease, but there are no efficient methods for diagnosis at early stage [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and mortality of bladder cancer have been significantly increased in the past decade [ 3 6 ]. Despite improvements in current clinical treatment such as surgery, adjuvant chemoradiotherapies, and immunological therapy, the prognosis of patients has not been significantly improved [ 7 11 ]. Patient's prognosis is closely related to the stage of the disease, but there are no efficient methods for diagnosis at early stage [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dyrskjøt et al [28] prospectively validated a 12-gene progression score for non-muscle invasive bladder cancer (NMIBC) and found that the prognostic power of this score was superior to histopathological parameters or clinical data. Ingelmo-Torres et al [29] constructed a predicting model based on two urinary cell microRNAs, miR-140-5p and miR-92a-3p. In this study, we developed a new prognostic index.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, we provided evidence that miRNAs can be used as prognostic biomarkers in UTUC in tissue samples [ 3 , 4 ]. On the other, we showed that miRNAs can be useful diagnostic and prognostic biomarkers for bladder cancer in urine samples [ 12 , 18 ]. Here, we evaluate circulating miRNA in the bloodstream from UTUC patients as minimally invasive predictive biomarkers of tumour progression and patient survival.…”
Section: Discussionmentioning
confidence: 99%